LMI-based 2-DoF control design of a manipulator via T-S descriptor approach. Issue 22 (2018) - Nguyen, Van-Anh; Nguyen, Anh-Tu; Dequidt, Antoine; Vermeiren, Laurent; Dambrine, Michel
Abstract: This paper presents a method for the control design of a manipulator. The design goal is to achieve a guaranteed H ∞ model reference tracking performance with respect to bounded reference inputs through a 2-DoF control scheme. To achieve this goal, the manipulator system is represented by a Takagi-Sugeno fuzzy model in descriptor form. The control scheme is based on a parallel distributed compensation controller. Furthermore, the stability of the nonlinear system is also guaranteed. Based on Lyapunov stability theory, the control design is formulated as an LMI optimization problem which can be effectively solved with numerical solvers. Simulation results carried out with the SimMechanics environment clearly demonstrate the effectiveness of the proposed method.